Working Memory Maturation: Can We Get At the Essence of Cognitive Growth? - Cowan, Nelson (Perspect Psychol Sci, 2016)
Our theoretical and practical understanding of cognitive development depends on working memory, the limited information temporarily accessible for such daily activities as language processing and problem-solving. Here I assess many possible reasons why working memory performance improves with development. A first glance at the literature leads to the weird impression that working memory capacity reaches adult-like levels during infancy but then regresses during childhood. In place of that unlikely surmise, I consider how infant studies may lead to overestimates of capacity if one neglects supports that the tasks provide, compared to adult-like tasks. Further development of working memory during the school years is also considered. Various confounding factors have led many investigators to suspect that working memory capacity may be constant after infancy; the factors include developmental increases in knowledge, filtering out of irrelevant distractions, encoding and rehearsal strategies, and pattern formation. With each of these factors controlled, though, working memory still improves during the school years. Suggestions are made for research to bridge the gap between infant and child developmental research, to understand the focus and control of attention in working memory and how they develop, and to pinpoint the nature of capacity and its development from infancy on.